Identification and validation of ferroptosis-related biomarkers in intervertebral disc degeneration - Li, Chenglong; Fei, Chengshuo; Le, Shiyong; Lai, Zhongming; Yan, Bo; Wang, Liang; Zhang, Zhongmin (Frontiers in Cell and Developmental Biology, 2024)
Ferroptosis plays an important role in intervertebral disc degeneration (IDD). We aim to identify key genes that regulate ferroptosis within IDD to uncover the fundamental mechanisms of the disease. we analyzed public datasets (GSE23130 and GSE70362) and the FerrDb database to identify ferroptosisrelated genes (DE-FRGs) involved in IDD, including MT1G, CA9, AKR1C1, AKR1C2, DUSP1, CIRBP, and KLHL24. Validation with single-cell RNA sequencing (GSE199866) confirmed the specific roles and expression patterns of these genes, particularly spotlighting the roles of MT1G and CA9. Subsequently, we used immunohistochemistry and Western blot analyses in both clinical and mouse models, the protein expression levels of these DE-FRGs in various tissues were identified. Additionally, we explored how these genes influence immune cell infiltration in the IDD microenvironment, highlighting potential immune-modulatory roles. Conclusively, our study elucidates the crucial role of ferroptosis in IDD and identifies specific genes as potential targets for diagnosis and therapy.